2016
DOI: 10.1007/s12011-016-0717-0
|View full text |Cite
|
Sign up to set email alerts
|

The Iodine Content in Urine, Faeces and Selected Organs of Rats Fed Lettuce Biofortified with Iodine Through Foliar Application

Abstract: Iodine is an essential trace element for humans. Foliar application of micronutrients is successfully used in order to increase the concentration of essential elements in vegetables. The aim of this study was to evaluate the iodine absorption in the rat organism fed foliar biofortified lettuce. The presented study was consisted of the vegetative and animal experiment. In the vegetative experiment with lettuce, two combinations of foliar application were used: (1) control—without iodine application and (2) iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Moreover, after KIO 3 treatment, the increase of crude fat content was noted as compared to control and other treatments. Other researchers who also studied the chemical composition of lettuce showed that the fertilization of iodine did not imply changes in nutrients content in plants [33,34].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, after KIO 3 treatment, the increase of crude fat content was noted as compared to control and other treatments. Other researchers who also studied the chemical composition of lettuce showed that the fertilization of iodine did not imply changes in nutrients content in plants [33,34].…”
Section: Discussionmentioning
confidence: 97%
“…Pi ątkowska et al [58] reported that the concentration of iodine in the urine of rats fed a diet with raw carrot biofortified with the non-organic form of iodine (KI) during agriculture was higher compared to the urine of rats fed a diet with the control carrot. Rakoczy et al [59] also showed similar results in an animal study in which rodents were fed a diet with lettuce. But they were still lower compared to the control group where the source of iodine was a mineral mix.…”
Section: Discussionmentioning
confidence: 61%
“…46 A study on 50 healthy volunteers, who consumed iodine-enriched potatoes, carrots, cherry tomatoes, and green salad, showed that the concentration of urinary iodine, which is the suggested indicator for determining the prevalence of IDDs, increased slightly but significantly as a result of the diet. 47 More thorough investigations on animal models demonstrated that eating biofortified carrots 48 or lettuce 49 enhanced iodine assimilation.…”
Section: Biofortification With Iodinementioning
confidence: 99%